XIV Modern Literature. Issue 1 (16th November 2020) - Ross, Shawna; Bratton, Francesca; Krzakowski, Caroline; Corser, Sophie; Keese, Andrew; Phillips, Joshua; West, Mark; Cooper, Samuel; D'Monte, Rebecca; Martín, Gustavo A Rodríguez; Saunders, Graham; Masud, Noreen; et al.
Abstract: This chapter has eight sections 1. General. 2. Fiction Pre-1945; 3. Fiction Post-1945; 4. Drama Pre-1950; 5. Drama Post-1950; 6. British Poetry 1900–1950; 7 British Poetry Post-1950; 8. Modern Irish Poetry. Section 1 is by Shawna Ross; section 2(a) is by Francesca Bratton; section 2(b) is by Caroline Krzakowski; section 2(c) is by Sophie Corser; section 2(d) is by Andrew Keese; section 2(e) is by Joshua Phillips; section 3(a) is by Mark West; section 3(b) is by Samuel Cooper; section 4(a) is by Rebecca D'Monte; section 4(b) is by Gustavo A. Rodríguez Martín; section 5 is by Graham Saunders; section 6(a) is by Noreen Masud; section 6(b) is by Matthew Creasy; section 7 is by Alex Alonso; section 8 is by Karl O'Hanlon.